KEANEKARAGAMAN JAMUR ARBUSKULA DI PULAU ENGGANO [Diversity of Arbuscular Fungi in Enggano Island] - Kramadibrata, Kartini (BERITA BIOLOGI, 2016)
A study on diversity of arbuscular fungi (AF) in forest area and small plantation in eastern part of Enggano island was done. Twelve species of AF were identified from this island. Eleven species had been reported from Java and associated with different kinds of plant, but three species i.e. Â Gigaspora gigantea, Glomus multicaule and Scutellospora heterogama were not common, while Sclerocystis taiwanensis is a new record for Indonesia. All species of AF recorded from this island were described by their morphological characters and their Â distribution in Enggano island were presented.